Heat Treatment for Elimination of Red-Halophiles from Contaminated Solar Salt - M.M., Prasad; C.C., Panduranga Rao (Fishery Technology, 2025)
In an effort to develop a suitable method for prevention of red-discolouration in cured fish, the efficacy of heat treatment was evaluated in eliminating red halophiles from contaminated salt samples. Naturally contaminated salt samples containing red halophiles as well as sterilized salt samples artificially contaminated with red-halophilic Cocci were employed in this study. Heating of contaminated salt at a temperature of SOC for 30 min, was found to be effective in eliminating red-halophilic Cocci.